Peran Orang Tua dalam Keberlangsungan Pendidikan Anak (Studi pada Masyarakat Perbatasan Malaysia di Desa Merakai Panjang Kabupaten Kapuas Hulu) - Kritiana Nawai; Imran Imran; Iwan Ramadhan; Suriyanisa Suriyanisa; Daniel Daniel (Jurnal Pendidikan : Riset dan Konseptual, 2023)
The purpose of this study was to determine the role of parents in the continuity of children's education in the Malaysian border community in Merakai Panjang Village, Kapuas Hulu District as motivators, facilitators, and as educators. The research was conducted using a descriptive qualitative approach. In collecting data techniques used are observation, interviews, and documentation. The data sources used are primary data sources and secondary data sources where the main data sources in qualitative research are words and actions, the rest are additional data such as documents and others. In analyzing the data using data reduction techniques, data presentation, and drawing conclusions. The results of this study indicate that the role of parents in the continuity of children's education in the Malaysian border community in Merakai Panjang Village, Kapuas Hulu District. Parents have instilled a spirit of nationalism so that children become successors who feel proud of education in Indonesia. Parents have also instilled the character and personality of children through education given by parents, as well as providing knowledge about love for the motherland so that they can respect the country with a high spirit of nationalism and patriotism.